Advanced statistics for kinesiology and exercise science a practical guide to ANOVA and regression analyses - Malek, Moh H.; Coburn, Jared W.; Marelich, William D. (Routledge, Taylor & Francis Group, 2019)
Based on lectures presented as part of the third European Foundation for Psychiatry at the Maudsley (EFPM) meeting, this book aims to show that genes and environment are both important, and may correlate or interact with one another. It is useful for psychiatrists, psychologists, epidemiologists and geneticists.